PERILAKU SELF-HARM SEBAGAI DAMPAK FENOMENA FATHERLESS - Salsabila, Kania Rosma (Jurnal Profesi Bimbingan dan Konseling, 2024)
Indonesia was named third in the "Fatherless country in the world" or a country that lacks a father's role both physically and psychologically. This problem is a hot topic of discussion in the world. Fatherless itself has a serious impact, especially for young girls. The method used in this research is literature review through journals, scientific articles, and also research related to the role of fatherless. the role of the father figure is very important for the growth of children, therefore families need to understand the role of each family member